A NAIRU assessment: an applied case to Colombia’s labor markets (2015)
Given the discrepancy over the optimum levels of employment for Colombia, this research targets both, the national and urban, Non-Accelerating Inflation Rate of Unemployment (NAIRU) for the Colombian markets -- In doing so, there is a strong pertinence in estimating the constant NAIRU through raw and minimally altered data and providing the reader with a complete brief of the theory in which the model is founded -- The introduction of supply shocks is considered to attain improved estimations and a more reliable assessment of the NAIRU to those that have previously been attempted -- The backbone of the analysis is conducted through the relationship established by the Phillips curve from 2001 until 2015